Pengaruh Experiential Marketing dengan Customer Loyalty di Rumah Sakit - Nindya Arifani Nurseha; Diansanto Prayoga (Media Gizi Kesmas, 2023)
Background: Studies on experiential marketing in various types of industries are proven to have an impact on customer loyalty. The increasing number of health care creates competition in the market. Hospitals are not spared from this competition so that the application of appropriate marketing is important to create customer loyalty. Objectives: This study was conducted to identify the effect of experiential marketing based on the indicators: sense, feel, think, act, and relate to customer loyalty in hospitals. Methods: Scoping Review was conducted using the guidelines from the JBI Manual for Evidence Synthesis. Searches were conducted on electronic databases including PubMed, Garuda, Indonesia Onesearch, and ScienceDirect. Results: The results showed that experiential marketing based on its indicators, namely sense, feel, think, act, and relate in hospitals has an effect on customer loyalty. Conclusions: Hospitals should be able to provide a pleasant experience for patients, one of which is by implementing experiential marketing.